Project performance factors in the domestic business support system in Kazakhstan: An empirical study - Gimranova, L.; Pritvorova, T.; Spanova, B.; Abeuova, S.; Serikova, G. (International Journal of Innovative Research and Scientific Studies, 2024)
The relevance of the study is due to the importance of assessing projects implemented within the framework of the state business support system, in which entrepreneurs take an active part by submitting applications for various types of support, including investment subsidies, technical assistance in the implementation of quality management systems, export support, and educational programs. The study identified the main factors determining the successful implementation of projects aimed at supporting and stimulating business development. The research design of project implementation effectiveness factors in the business support system is a strategic approach that allows you to organize and structure the analysis of theoretical concepts, and also provides a basis for subsequent experimental research in a real practical project management environment. The research methodology includes the use of structural modeling, which is a validated technique for testing multiple parallel hypotheses about the existence of cause-and-effect relationships. The conducted survey of business entities in several regions of Kazakhstan and the subsequent data analysis confirmed the significance of the identified factors, as a result of which the identified analysis allows to better understand the processes occurring in the business support system and offer practical recommendations for its improvement, which can also serve as a basis for the development of more effective strategies and programs to support entrepreneurship in Kazakhstan
Keywords: Business; Government support; Influencing factors; Project approach; Public administration; SmartPLS model